The Influence of Spiritual Leadership Style, Motivation, and Organizational Culture on the Performance of Employees at BAPPEDA (Regional Development Planning Agency) of Jember Regency Government - Herawati, Nanda Dwi; Tyas, Wenny Murtalining; Winahyu, Pawestri (Ilomata International Journal of Management, 2025)
Employee performance is one of the main factors that determine an organization's effectiveness in achieving goals, especially in the public sector, such as the BAPPEDA Jember Regency. However, challenges such as weak motivation, suboptimal implementation of organizational culture, and non-integrated leadership styles often become obstacles to achieving maximum performance. This research aims to analyze the influence of Spiritual Leadership Style, Motivation, and Organizational Culture on Employee Performance at BAPPEDA Jember Regency. The research uses quantitative methods with a survey approach. Data was collected through a questionnaire distributed to all BAPPEDA Jember Regency employees using a total sampling technique with 53 respondents. Data analysis was carried out using multiple linear regression to test the influence of the independent variable on the dependent variable. The research results show that, partially, spiritual leadership style and motivation have a significant influence on employee performance, while organizational culture does not have a significant influence. Simultaneously, these three variables have a significant influence on employee performance, with a contribution of 79.9% (R² = 0.799). This research concludes that strengthening motivation and implementing leadership based on spiritual values ​​is very important to improve employee performance. Meanwhile, the development of a more adaptive organizational culture needs to be strengthened to support sustainable organizational performance.